Early-onset Colorectal Cancer is Distinct From Traditional Colorectal Cancer - Yeo, Heather; Betel, Doron; Abelson, Jonathan S.; Zheng, Xi E.; Yantiss, Rhonda; Shah, Manish A. (Clinical colorectal cancer, 2017)
Early-onset colorectal cancer (E-CRC) is increasing. We sought to characterize differences between E-CRC and traditional (T-CRC). We used the National Surveillance, Epidemiology, and End Results database, the Behavioral Risk Factor Surveillance Survey, and The Cancer Genome Atlas (TCGA). We compared demographics, tumor characteristics, and incidence of early onset compared to traditional onset colorectal cancer. E-CRC tumors are clinically, pathologically, and molecularly distinct from T-CRC. Early-onset colorectal cancer (E-CRC) is increasing in incidence, unlike traditional CRC (T-CRC). We sought to characterize differences between E-CRC and T-CRC. Data sources included the Surveillance, Epidemiology, and End Results database, the Behavioral Risk Factor Surveillance Survey, and The Cancer Genome Atlas (TCGA). We compared demographics, tumor characteristics, and incidence of CRC in subjects aged 20 to 49 years (E-CRC) with those aged ≥ 50 years (T-CRC). We correlated the incidence of E-CRC and T-CRC to CRC risk factors and age-dependent genomic characteristics of CRC using TCGA. A total of 369,796 CRCs were identified (2000-2011). E-CRC incidence has risen 1.4% per year, whereas T-CRC has declined 3.1% per year (P < .05). The incidence of E-CRC increases in a step-wise fashion from the ascending colon to rectum (P < 2.2e−16). E-CRC is more prevalent in male (53.7% vs. 46.4%; P < .001), Black (14.6% vs. 11.0%; P < .001), and Hispanic (14.7% vs. 8.3%; P < .001) patients. E-CRC presents with aggressive histology, including high-grade (1.5% vs. 1.3%; P < .001), signet ring cell (1.9% vs. 0.9%; P < .001), and mucinous carcinomas (8.9% vs. 8.1%; P < .001), and more often with distant disease (24.4% vs. 18.8%; P < .001). The geographic distribution of E-CRC mirrors United States counties with higher Black population densities. Unlike T-CRC, E-CRC prevalence is not correlated with known CRC risk factors. E-CRC is associated with a lower rate of mutations than traditional CRC. Limitations of this study include E-CRC sample size for the TCGA analysis, as well as lack of comorbidity information and family history. E-CRC tumors are clinically, pathologically, and molecularly distinct from T-CRC. Further evaluation of genetic and molecular differences is necessary to understand the pathophysiology of E-CRC and to help target treatment/surveillance strategies.